Normolipemic xanthomatosis. Issue 839 (September 1995) - Handa, R.; Gupta, K.; Wali, J. P.
Abstract : A 20-year-old woman presented with tendon and tuberous xanthomas. Plasma lipid levels were normal. Xanthomatosis with normal lipid levels is rare.